Evaluating the Effectiveness of Professional Development Programs for Junior High School Mathematics Teachers in Improving Mathematics Instruction in the K to 12 Curriculum in the Philippines - Dicdiquin, Juana B.; Mobo, Froilan D.; Cutillas, Anesito L. (Future Science / FSH-PH Publications, 2023)
This study assessed the effectiveness of a professional development program for junior high school mathematics teachers in the Philippines and analyzed their achievement test results in Mathematics. The study aimed to identify the factors affecting the quality of mathematics instruction and propose solutions to these challenges. The study found that while most teachers were consistent in their lesson planning and content delivery, they need to improve their questioning techniques, differentiated techniques, and strategies to develop higher-order thinking skills. The study suggests that teachers need to enhance their teaching practices to achieve the K to 12 Curriculum goals, prepare students for better work opportunities, and contribute to the nation's economy. Professional development programs can provide opportunities for mathematics teachers to increase their knowledge and confidence in the subject. By improving their teaching practices, teachers can help enhance the quality of mathematics education in the Philippines. This study highlights the challenges mathematics teachers face in the country and the need for professional development programs to help them improve their teaching practices. The findings have important implications for mathematics education in the country, which can help raise the quality of education and the nation's economy.